IgA antibodies against Streptococcus mutans in breast milk and saliva: Passive Immunity against caries - Mitterhofer, Werônica Jaernevay Silveira; Sherma, Alexandre Prado; dos Santos, Silvana Soléo Ferreira; Leão, Mariella Vieira Pereira (Brazilian Dental Science, 2019)
Objective: The present work aimed to correlate the levels of IgA antibodies reactive with Streptococcus mutans antigens in the saliva and/or in the breast milk and the oral health of lactating. Material and methods: Breast milk and whole saliva samples were collected from 29 lactating. The oral health was verified using DMF scores and the volunteers were separated in three groups: 1) low DMF score; 2) high DMF score with active caries and 3) high DMF score without active caries. The IgA antibodies anti-Streptococcus mutans were analyzed in the samples using ELISA technique. Results: The results showed similar levels of IgA antibodies in all groups, both in milk and saliva. No correlation could be confirmed between the levels of IgA in the saliva and in the breast milk with the oral health of lactating studied. Conclusion: The results suggest that, independently of mother’s oral health, the newborn receive the same amounts of anti-Streptococcus mutans IgA by breastfeeding.